Índice de vulnerabilidade das famílias (2000-2010): Resultados - Bernardo Alves Furtado (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– The objective of this paper is to make available information - precisely and spatially detailed - about families' vulnerabilities derived from questionnaires' answers of census data for 2000 and 2010. In doing so this paper fulfills the task of providing reference data - occasionally complex - accessible to public authorities and researchers so that inferences can be made from the micro data of the census sample interviews. The methodology used is by and large detailed in the literature. The actual construction of the indicators is based on the analysis of presence or absence of vulnerabilities within families across six different dimensions, detailed for the country, states, municipalities and intraurban detail. Results indicate that Brazilian families' vulnerability reduced by nearly 20% in the period on average. This behavior, however, is heterogeneous among the dimensions analyzed, the indicators or the regions and states of the country. It is exactly the analysis of this perceived heterogeneity in the decade that makes the core of the contribution of this paper.
Keywords: C81; R20; I32; 330; indices; vulnerability; families; census; spatial analysis